APPLICATION FOR ELECTRICAL POWER SERVICE ADDITION RATES USING VISUAL BASIC 6.0 - Maria Ulfah; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2004)
Power adder is an electric power where consumers want to add electric power at a company or other installations, namely as: Social, Household, Business Industrial, Bulk. Where a company or a home you want to increase the electric power with the first 450 VA to 900 VA. At this time the company is still dealing with consumers who want to add new resources with memeberikan new information to the advertiser before completing the notice of the new posters need to know for the initial power to the new power will make the price of electricity will notify all of them, for example, the initial power your house VA 450 to 900 VA. This power adder applications programs is one alternative to solve existing problems. This program requires Windows-based computer, the program made the application, can help the company increase its electrical power.